BUDIDAYA SACHA INCHI (Plukenetia volubilis L.), PASCAPANEN, DAN PRODUK OLAHANNYA DI KELOMPOK TANI FENUN, DESA BAUMATA, KABUPATEN KUPANG, PROVINSI NUSA TENGGARA TIMUR - I Gusti Bagus Adwita Arsa; Yosep Seran Mau; Herianus J. D. Lalel; I Gusti Made Budiana; Marselina Yohana Aku (Jurnal Abdi Insani, 2025)
Sacha Inchi cultivation is not yet known in Baumata Village, Kupang Regency. Therefore, cultivation needs to be carried out because the various benefits of this plant’s products are very important for the health of the local community. Sacha Inchi can serve as an important source of nutrients that may help address malnutrition and cardiovascular diseases. With its high protein and healthy fat content, Sacha Inchi can be an alternative source of protein that is more affordable and accessible compared to animal-based protein sources. This activity aims to introduce Sacha Inchi cultivation to the Fenun Farmers Group in Baumata Village and to assess their level of acceptance toward cultivation techniques, post-harvest handling, and processed products made from Sacha Inchi. The method involves introducing an existing cultivation model from the Dryland Research Station of Undana, conducting outreach on cultivation, post-harvest handling, and processed Sacha Inchi products, followed by practical training at the Dryland Research Station of Undana, and continuing with practice of cultivation and processing  on the Fenun farmers group’s place. The activity enabled farmers to learn Sacha Inchi cultivation techniques, starting from seed germination, seedling production, planting, and crop maintenance. The germination method used resulted in 85–90% seed germination, 100% healthy seedling growth, and 100% successful growth of plants in the field. Farmers also learned how to peel Sacha Inchi fruits into raw materials ready for processing and how to make Sacha Inchi seed–based products such as roasted nuts, cookies, brownies, and vegetable oil. Coclusion: The Fenun farmers group successfully cultivated Sacha Inchi plants and were able to carry out post-harvest handling and product processing effectively.